Implementasi model Dynamic Systems Development untuk mengembangkan sistem informasi coffe shop berbasis website - Elungan, Owen Vanessa Ariella; Sulaksono, Aditya Galih (Universitas Merdeka Malang, 2024)
The trend of Micro, Small and Medium Enterprises (MSMEs) in the form of coffee shops continues to grow in Indonesia, including those that are currently often found in the Kepanjen area, Malang Regency. For communication needs, these shops form a community as a means of sharing information. Even though there are many benefits gained from the community, the platforms used are still limited to social media. This research aims to develop a website-based information system which will make it easier to manage activities that are being or will be carried out by the coffee shop community in the Kepanjen area. The Dynamic Systems Development model is used in this research as a benchmark for developing information systems. The results of system functional testing show that the website built can run well and is suitable for use. Through this information system, coffee shop owners located in Kepanjen can register to be promoted on the website. Apart from that, the information system created can make it easier to find information about coffee shops in the Kepanjen area.